Pengaruh Kewajiban Penyediaan Modal Minimum dan Non-Performing Financing Terhadap Cadangan Kerugian Penurunan Nilai Pada PT. Bank KB Bukopin Syariah - Setiawan , Dimas; Ibrahim, Zaini; Wulandari, Soliyah (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2024)
The study aims to determine the effect of Minimum Capital Provision Obligations on Impairment Loss Reserves, the effect of Non-Performing Financing on Impairment Loss Reserves, and the simultaneous effect of Minimum Capital Provision Obligations and Non-Performing Financing on Impairment Loss Reserves. Research in the form of secondary data on quarterly financial statements for 2015-2022, data collection techniques, literature studies, and documentation techniques. Research sample at PT. Bank KB Bukopin Syariah, purposive sampling method sampling technique. Multiple linear regression analysis research methods: normality test, multicollinearity, autocorrelation, heteroscedasticity, descriptive statistics, t test, F test, correlation coefficient, and determination coefficient. Partial conclusion, Minimum Capital Provision Obligation has no effect on Impairment Loss Reserves based on sig. value 0.09 > 0.05, while Non-Performing Financing has a positive and significant effect on Impairment Loss Reserves based on sig. value 0.00 < 0.05. Simultaneous conclusion, Minimum Capital Provision Obligation and Non-Performing Financing affect Impairment Loss Reserve with a value of sig. 0.00 < 0.05. R value of 0.85% means that Minimum Capital Provision Obligations and Non-Performing Financing against Impairment Loss Reserves have a very strong relationship. The R2 value of 70.1% means that the Impairment Loss Reserve is influenced by Minimum Capital Provision Obligations and Non-Performing Financing, and the remaining 29.9% is influenced by other variables.